A study on compliance of safety belt usage among car drivers in district of Batu Pahat, Johor - Ambak, Kamarudin (2007)
Cars are the second (40%) most common mode of transportation in Malaysia. In terms of fatal road accidents, car drivers constitute about 9.0% and passengers 13.6% of fatalities. The major cause of car occupants’ fatality in such accidents is head injuries, which consist of more than half (56.4%) of the fatalities. Thus restraining the head and body, the initial position is the most important injury control strategy for car users. The use of seat belts was deemed one of the most effective ways to reduce road accident fatalities in Malaysia and consequently the mandatory seat belt law was enforced in the early seventies. This paper presents the method of how to determine the level of practice of safety belt usage among car drivers in Batu Pahat and to identify the target group who are most likely to violate the safety belt law. A questionnaire study was carried out in Batu Pahat, Johor on the compliance behavior of car occupants in relation to seat belt use. A total of 218 respondents were interviewed and the data was analyzed using chi-square method. Three variables were found to be significant at percent level (p<0.05): travel distance, location of travel and day of travelling. Compliance with the seat belt law was higher among drivers, educated car users, in the presence of enforcement activities, traveling in city-center areas and car users with a positive attitude towards the risks of speeding.